1986
DOI: 10.1007/bf00848474
|View full text |Cite
|
Sign up to set email alerts
|

Tailored media can enhance the success of smoking cessation clinics

Abstract: Smokers recruited through the medical outpatient clinics of two similar Veterans Hospitals over two successive years participated in a smoking cessation study which randomized them between a group assigned to behavior modification clinics and a group receiving a packet of smoking cessation material in the mail. Following the second year's clinics at the site of one of the two hospitals, an intensive media campaign, based on the content of the behavior modification program, was targeted at the study population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Participants who believed they would be successful in their attempts to quit tended to have more success than those without as much faith in quitting smoking, consistent with findings by Dyer (1983), Mogielnicki et al (1986), andBen-Sira (1982). Past studies have shown self-efficacy to be strongly related to success in quitting smoking with many different types of cessation programs (Mothersill et al, 1988) and televised self-help clinics (Best, 1980;Wheeler, 1987).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Participants who believed they would be successful in their attempts to quit tended to have more success than those without as much faith in quitting smoking, consistent with findings by Dyer (1983), Mogielnicki et al (1986), andBen-Sira (1982). Past studies have shown self-efficacy to be strongly related to success in quitting smoking with many different types of cessation programs (Mothersill et al, 1988) and televised self-help clinics (Best, 1980;Wheeler, 1987).…”
Section: Discussionsupporting
confidence: 79%
“…Because past research suggested personal testimonies of ex-smokers to increase participant chances of remaining abstinent, a variety of vignettes was also interspersed throughout the show to help motivate the smokers to quit (Mogielnicki et al, 1986).…”
Section: Program Design and Implementationmentioning
confidence: 99%
“…164 -166,214 -234 An additional 14 reports provided more information on an already-included study. 152,161,[235][236][237][238][239][240][241][242][243][244][245][246] Four reports with limited quality of execution 214,219,227,233 and two reports with least-suitable study designs 216,232 were not included in the body of evidence. Three studies measured the effect of a mass media campaign in increasing use of a telephone cessation information service, 215,229,231 and these results are described later in this section in the review of multicomponent interventions including patient telephone support.…”
Section: Mass Media Education: Campaignsmentioning
confidence: 99%
“…Mogielnicki et al (1986) and Ockene and Camic (1985) found that mass media can have a positive effect on long-term smoking cessation, especially when combined with collateral advertising on different levels. The goal in AIDS prevention is after all not just to induce people to use a condom once, but to change their attitudes in order to influence their long-term behavior.…”
Section: Psychological Characteristics Of Restroomsmentioning
confidence: 99%